2017
DOI: 10.24059/olj.v21i1.843
|View full text |Cite
|
Sign up to set email alerts
|

Online Learning Integrity Approaches: Current Practices and Future Solutions

Abstract: The primary objective of this paper is to help institutions respond to the stipulation of the Higher Education Opportunity Act of 2008 by adopting cost-effective academic integrity solutions without compromising the convenience and flexibility of online learning. Current user authentication solutions such as user ID and password, security questions, voice recognition, or fingerprint identification are not infallible and may violate students' rights to privacy or cause undue interruptions to their efforts in pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 20 publications
1
46
0
1
Order By: Relevance
“…Development of online learning assessment methods as rigorous as in conventional face-to-face setting to prevent cheating/plagiarism is not straightforward [ 16 , 29 ]. While one cannot propose a single assessment method that would work ideally for all engineering courses and classroom sizes, it would still be interesting to study how various online exams and assessment methods (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Development of online learning assessment methods as rigorous as in conventional face-to-face setting to prevent cheating/plagiarism is not straightforward [ 16 , 29 ]. While one cannot propose a single assessment method that would work ideally for all engineering courses and classroom sizes, it would still be interesting to study how various online exams and assessment methods (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Designing a fair, equitable, and rigorous assessment to minimize cheating and plagiarism is difficult in online environment [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…He expresses that internet can be a tool for fast and easy cheating. The results of the study of Lee-Post and Hapke (2017) indicate that 45% of their learners found the cheating easy in online courses and 30% learners affirm that they would not hesitate to cheat if they get an opportunity to do it. The participants of the study of Kocdar, Karadeniz, Peytcheva-Forsyth and Stoeva (2018), while responding to the open-ended questions have shown their sensitivity towards the subject of cheating and plagiarism and have clarified their position on the subject.…”
Section: Resultsmentioning
confidence: 98%
“…In the last decade, innovative learning approaches have been introduced into the higher education system. The development of technology and its prevalent use have led higher education institutions to introduce online courses, either fully online or hybrid courses, into their academic learning programs (Lee-Post & Hapke, 2017 ; Marshall & Varnon, 2017 ). This approach enables an increase in full and easy access to learning contents, use of social media, Wikipedia, sharing sites, etc.…”
Section: Introductionmentioning
confidence: 99%
“…This approach enables an increase in full and easy access to learning contents, use of social media, Wikipedia, sharing sites, etc. (Ahmed, 2018 ; Lee-Post & Hapke, 2017 ; Peytcheva-Forsyth et al, 2018 ). In fact, digital technology such as Smartphones, palm computers, mobile computers and PCs and the Internet enable more flexibility, creativity and sometimes even accuracy and effectiveness.…”
Section: Introductionmentioning
confidence: 99%